Assessing sexual health literacy among Thai female adolescents in non-formal education: A mixed-methods study - Narkbubpha, Rapeepan; Sriyasak, Atcharawadee; Sarakshetrin, Atiya; Thungthin, Pailin (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Adolescent pregnancy in Thailand and globally remains a major public health issue, often leading to significant health and social consequences. Among adolescents outside the formal education system, low levels of sexual and reproductive health literacy contribute to poor decision-making and increased risk of unintended pregnancy. Targeted, culturally sensitive interventions are essential to bridge these gaps and reduce associated hardships. Objective: This study aimed to evaluate the sexual health literacy of Thai female adolescents in non-formal education, focusing on their knowledge levels, decision-making processes, and barriers to accessing accurate sexual health information and services. Methods: A mixed-methods sequential explanatory design was used. Quantitative data were collected between November 2021 and September 2022, and qualitative data between December 2022 and August 2023. Multi-stage random sampling was used to select 270 participants aged 15–19 from non-formal education programs, yielding a final sample of 200 after excluding incomplete data (response rate = 74.07%). The qualitative phase involved semi-structured interviews with 30 participants who scored low on the sexual health literacy assessment. Information was gathered through semi-structured interviews to explore their knowledge and decision-making process. Descriptive statistics were used to analyze the quantitative data, and thematic analysis was used to analyze the qualitative responses. Results: Participants demonstrated moderate overall sexual health literacy (M = 97.73, SD = 16.91). Decision-making regarding sexual practices scored the highest (88.79%), while access to health information and services scored the lowest (54.72%). Thematic analysis revealed four major themes: 1) The need for supplemental sexual education beyond formal classrooms, 2) Widespread misconceptions and reliance on unreliable contraceptive information sources, 3) Limited access to sexual health services for adolescents, and 4) The decision-making process prior to selecting a contraceptive method. Conclusion: There is a clear need for targeted, comprehensive sexual health literacy programs that improve adolescents’ knowledge, communication skills, and understanding of contraception. Engaging mothers and other female relatives as key influencers, along with the involvement of nurses and youth-friendly service providers, is essential. These initiatives should focus on preventing high-risk behaviors, delaying sexual initiation, and reducing unplanned pregnancies, especially in underserved non-formal education contexts.